Capitalizing on Economic Function of the Institution of Zakāt in Modern Economy - Salman Ahmed Shaikh (Center of Strategic Studies (PUSKAS) BAZNAS, 2018)
This study analyzes the economic potential of the institution of Zakāt on income redistribution, poverty and aggregate demand. Through a mathematical exposition, we show that if a person keeps idle investible wealth, then Zakāt will deplete the idle wealth over time. On the macroeconomic front, proportional Zakāt linked with income will act as an automatic stabilizer. If an economy is in disequilibrium and policies fail to immediately recover and boost incomes, wealth Zakāt will enable the distributive allocation that works independently of the business cycles and will help in stabilizing the extremes of the business cycles. In this way, wealth Zakāt will act as a permanent stabilizer. We discuss that Zakāt is an important tool for redistributing income and it can also increase aggregate spending. The redistribution from people with lower MPC to people with higher MPC will boost aggregate spending even with the same level of aggregate income. Finally, we recommend certain steps at the policy and implementation level so that the institution of Zakāt can be effectively utilized to contribute in poverty alleviation. We recommend that it is appropriate to disburse Zakāt at the federal level. This way, the regional disparities can be reduced more effectively. To gain the trust and the confidence of people, it is vital to improve the governance and transparency. In this regard, we recommend that the Zakāt collection and disbursement details shall be reported in a standard way periodically. We also highlight the importance of creating synergies between Zakāt and other welfare programs. We also draw attention towards modifying the accounting standards to achieve transparent computation, assessment and collection.